Charcot arthropathy: The diagnostic dilemma of a painless, destructive joint. Issue 1 (11th December 2019) - Galanis, Nikiforos; Kyriakou, Aikaterini; Delniotis, Ioannis; Charanidi, Paraskevi; Mavropoulos, Paraskevas; Inklebarger, James
Abstract: The impressive clinical picture of Charcot joint reflects a high energy trauma injury which in the contrary is a progressive, painless arthropathy. Early and accurate diagnosis is crucial. A favorable outcome is elicited when joint is treated promptly, while late or misdiagnosis may lead to amputation. Abstract : The impressive clinical picture of Charcot joint reflects a high energy trauma injury which in the contrary is a progressive, painless arthropathy. Early and accurate diagnosis is crucial. A favorable outcome is elicited when joint is treated promptly, while late or misdiagnosis may lead to amputation.